Challenges in comparing land subsidence measurements by PS-InSAR with simulations from coupled hydro-geomechanical modelling: a case study in Antwerp Harbour - A. Choopani; P. Orban; P. Y. Declercq; X. Devleeschouwer; A. Dassargues (Hydrogeology Journal, 2025)

Northern Europe’s suitability for offshore European flat oyster (Ostrea edulis) habitat restoration based on population dynamics - Brecht Stechele; Leo Barbut; Geneviève Lacroix; Luca A. van Duren; Vera Van Lancker; Steven Degraer; Giacomo Montereale Gavazzi; Peter Bossier; Annelies M. Declercq; Nancy Nevejan (Frontiers in Marine Science, 2023)
Introduction European and member state legislation encourage the sustainable development of offshore environments, with the restoration or creation of flat oyster ( Ostrea edulis ) habitats offering potential solutions to enhance biodiversity and provide ecosystem services. The site selection and identification of suitable habitats for flat oyster habitat restoration projects remains a significant knowledge gap. Methods By combining seabed substrate information with a coupled population (Dynamic Energy Budget - Individual-Based Models) and particle tracking model (for larvae dispersal), critical insights can be gained into the spatial distribution of suitability indicators such as population growth, fitness, reproduction, and self-recruitment. By applying this model to the English Channel and the North Sea over a ten-year period, suitable locations for flat oyster habitat restoration, restorative aquaculture, or oyster-related nature-inclusive designs can be identified. Comparing historical oyster bed locations with model outputs offers insights into why these locations were suitable for oyster bed development and allows for validation of the proposed approach. Results and discussion Coastal and nearshore environments are generally more suitable for flat oyster habitat restoration, and populations will grow more quickly in these areas. Offshore restoration in the North Sea presents challenges if it relies solely on self-recruitment. Besides site selection purposes, the model can be used to evaluate the effect of management strategies (e.g., initial population size) or environmental pressures (e.g., climate change, pollution) on restorations success.

OS03-07: Photobiomodulation Controls Keratinocytes Inflammatory Response through Nrf2 and Reduces Langerhans Cells Activation - S. Salman; C. Guermonprez; L. Peno-Mazzarino; E. Lati; A. Rousseaud; L. Declercq; S. Kerdine-Römer (Toxicology Letters, 2023)

Chemical and Water-Isotope Composition Unravels the Source and Evolution of the Kittilä Underground Mine Water, Kiistala, Finland - V. Milesi; J. Declercq; W. Harding; T. Jarman; O. Baas; J. Saukkoriipi; A. van Wageningen; R. Bowell (Mine Water and the Environment, 2023)

Correction to: Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

Lifestyle factors and lung cancer risk among never smokers in the Canadian Partnership for Tomorrow’s Health (CanPath) - Rachel A. Murphy; Maryam Darvishian; Jia Qi; Yixian Chen; Quincy Chu; Jennifer Vena; Trevor J. B. Dummer; Nhu Le; Ellen Sweeney; Vanessa DeClercq; Scott A. Grandy; Melanie R. Keats; et al. (Cancer Causes & Control, 2022)

The relationship between anthropometric measures and cardiometabolic health in shift work: findings from the Atlantic PATH Cohort Study - Ellen Sweeney; Zhijie Michael Yu; Trevor J. B. Dummer; Yunsong Cui; Vanessa DeClercq; Cynthia Forbes; Scott A. Grandy; Melanie Keats; Louise Parker; Anil Adisesh (International Archives of Occupational and Environmental Health, 2020)

Influence of the bordering shelves on nutrient distribution in the Arctic halocline inferred from water column nitrate isotopes - F. Fripiat; M. Declercq; C. J. Sapart; L. G. Anderson; V. Bruechert; F. Deman; D. Fonseca‐Batista; C. Humborg; A. Roukaerts; I. P. Semiletov; F. Dehairs (Limnology and Oceanography, 2018)
The East Siberian Sea and contiguous western Arctic Ocean basin are characterized by a subsurface nutrient maximum in the halocline, generally attributed to both Pacific inflow and intensive remineralization in shelf bottom waters that are advected into the central basin. We report nitrogen and oxygen isotopic measurement of nitrate from the East Siberian Sea and western Eurasian Basin, in order to gain insight into how nitrate is processed by the microbial community and redistributed in the Arctic Ocean. A large decoupling between nitrate δ 15 N and δ 18 O is reported, increasing and decreasing upward from the Atlantic temperature maximum layer toward the surface, respectively. A correlation between water and nitrate δ 18 O indicates that most of the nitrate (> 60%) at the halocline has been regenerated within the Arctic Ocean. The increase in nitrate δ 15 N correlates with the fixed N deficit, indicating a causal link between the loss of fixed N and the 15 N enrichment. This suggests that a significant share of benthic denitrification is driven by nitrate supplied by remineralization and partial nitrification, allowing residual 15 N‐enriched ammonium to diffuse out of the sediments. By increasing nutrient concentrations and fixed N deficit in shelf bottom waters, this imprint is attenuated offshore following advection into the halocline by nitrate regeneration and mixing. Estimation of the sedimentary isotope effect related to benthic denitrification yields values in the range of 2.4–3.8‰, with its magnitude driven by both the degree of coupling between remineralization and nitrification, and fixed N concentrations in shelf bottom waters.

First isolation of Vibrio tapetis and an atypical strain of Aeromonas salmonicida from skin ulcerations in common dab ( Limanda limanda ) in the North Sea - M Vercauteren; E De Swaef; A Declercq; L Bosseler; S Gulla; S Balboa; J L Romalde; L Devriese; H Polet; F Boyen; K Chiers; A Decostere (Journal of Fish Diseases, 2018)
Skin ulcerations rank amongst the most prevalent lesions affecting wild common dab ( Limanda limanda ) with an increase in prevalence of up to 3.5% in the Belgian part of the North Sea. A complex aetiology of these ulcerations is suspected, and many questions remain on the exact factors contributing to these lesions. To construct the aetiological spectrum of skin ulcerations in flatfish, a one‐day monitoring campaign was undertaken in the North Sea. Fifteen fish presented with one or more ulcerations on the pigmented and/or non‐pigmented side. Pathological features revealed various stages of ulcerations with loss of epidermal and dermal tissue, inflammatory infiltrates and degeneration of the myofibers bordering the ulceration, albeit in varying degrees. Upon bacteriological examination, pure cultures of Vibrio tapetis were retrieved in high numbers from five fish and of Aeromonas salmonicida in one fish. The V. tapetis isolates showed cross‐reactivity with the sera against the representative strain of serotype O2 originating form a carpet‐shell clam ( Ruditapes descussatus ). Moreover, the A. salmonicida isolates displayed a previously undescribed vapA gene sequence (A‐layer type) with possible specificity towards common dab. Further research is necessary to pinpoint the exact role of these agents in the development of skin ulcerations in common dab.

Sickeningly Sweet: L‐rhamnose stimulates Flavobacterium columnare biofilm formation and virulence - M D Lange; B D Farmer; A M Declercq; E Peatman; A Decostere; B H Beck (Journal of Fish Diseases, 2017)
Flavobacterium columnare , the causative agent of columnaris disease, causes substantial mortality worldwide in numerous freshwater finfish species. Due to its global significance and impact on the aquaculture industry continual efforts to better understand basic mechanisms that contribute to disease are urgently needed. The current work sought to evaluate the effect of L‐rhamnose on the growth characteristics of F. columnare . While we initially did not observe any key changes during the total growth of F. columnare isolates tested when treated with L‐rhamnose, it soon became apparent that the difference lies in the ability of this carbohydrate to facilitate the formation of biofilms. The addition of different concentrations of L‐rhamnose consistently promoted the development of biofilms among different F. columnare isolates; however, it does not appear to be sufficient as a sole carbon source for biofilm growth. Our data also suggest that iron acquisition machinery is required for biofilm development. Finally, the addition of different concentrations of L‐rhamnose to F. columnare prior to a laboratory challenge increased mortality rates in channel catfish ( Ictalurus punctatus ) as compared to controls. These results provide further evidence that biofilm formation is an integral virulence factor in the initiation of disease in fish.

Isolation and characterization of Pseudomonas syringae pv. porri from leek in Flanders - S. Rombouts; J. Van Vaerenbergh; A. Volckaert; S. Baeyen; T. De Langhe; B. Declercq; R. Lavigne; M. Maes (European Journal of Plant Pathology, 2016)

β-Alanine does not act through branched-chain amino acid catabolism in carp, a species with low muscular carnosine storage - F. Geda; A. Declercq; A. Decostere; A. Lauwaerts; B. Wuyts; W. Derave; G. P. J. Janssens (Fish Physiology and Biochemistry, 2015)

White necrotic tail tips in estuary seahorses, Hippocampus kuda , B leeker - A M Declercq; K Chiers; W Van den Broeck; A Rekecki; S Teerlinck; D Adriaens; F Haesebrouck; A Decostere (Journal of Fish Diseases, 2014)

Antimicrobial susceptibility pattern of F lavobacterium columnare isolates collected worldwide from 17 fish species - A M Declercq; F Boyen; W Van den Broeck; P Bossier; A Karsi; F Haesebrouck; A Decostere (Journal of Fish Diseases, 2013)
Flavobacterium columnare is the causative agent of columnaris disease in diverse fish species worldwide. Although columnaris is an important disease, the antimicrobial susceptibility pattern of F . columnare is not well studied. Thus, the purpose of this study was to test the in vitro antimicrobial susceptibility of 97 F . columnare isolates collected worldwide between 1987 and 2011 from 17 fish species. The broth microdilution technique was utilized for reliable testing of these fastidious organisms. None of the isolates displayed acquired resistance to florfenicol, gentamicin, ormetoprim‐sulfadimethoxine and trimethoprim‐sulfamethoxazole. Acquired resistance to chloramphenicol was detected in 1%, to nitrofuran in 5%, to oxytetracycline in 11% and to enrofloxacin, flumequine and oxolinic acid in 10%, 16% and 16% of the isolates, respectively, as reflected by a bimodal or trimodal distribution of their minimum inhibitory concentrations ( MIC s). One isolate showed acquired resistance towards several antimicrobial agents including erythromycin. Another isolate revealed acquired resistance towards – amongst others – ampicillin. The isolates displaying acquired resistance originated from ornamental fish species or V ietnamese catfish, except for two isolates coming from wild channel catfish in which acquired resistance was encountered towards oxytetracycline only. Fifty per cent of the resistant isolates from ornamental fish were shown to have acquired resistance against three classes of antimicrobial agents, assigning these isolates as multiple resistant. These data might indicate less prudent use of antimicrobials especially in ornamental fish species.